Contexts shaping the development and success of elite sport systems: a scoping review - Ramos, R.; De Bosscher, V.; Pankowiak, A.; Valleser, C. W. (Sport Management Review, 2023)
The importance of contexts in analysing elite sport systems and policies, as reflected in substantial research over the past couple of decades, is considered to nurture or constrain the development and outcome of elite sport systems toward international sporting success. Theorising elite sport systems as institutions operating and embedded in an open system may provide insight into the "hows" (throughput processes) and the "whys" (conditions) of the effectiveness of sport systems and policies to determine what may work (or not work) for each country`s specific context. This scoping review aims to examine and map determinants of elite sport development in nations. Specifically, the review analysed how studies: (1) theorised the determinants, (2) used terms to denote contextual determinants for elite sport development and success and (3) described or conceptualised context. Further, the review identified context dimensions derived from the elite sport development determinants. The scoping review identified 19 studies that contain relevant contextual determinants. Findings present seven context dimensions derived from a neo-institutional organisation framework that pertain to different institutional contexts that may influence the development of elite sport policy systems. An improved conceptualisation of context may enhance our understanding of the relationship between processes (i.e., sport policy mechanisms) and contexts.